2010
DOI: 10.1519/jsc.0b013e3181dc4330
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder Injuries Attributed to Resistance Training: A Brief Review

Abstract: The popularity of resistance training (RT) is evident by the more than 45 million Americans who engage in strength training regularly. Although the health and fitness benefits ascribed to RT are generally agreed upon, participation is not without risk. Acute and chronic injuries attributed to RT have been cited in the epidemiological literature among both competitive and recreational participants. The shoulder complex in particular has been alluded to as one of the most prevalent regions of injury. The purpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 50 publications
0
42
1
3
Order By: Relevance
“…This result was anticipated to occur from a training effect as the deltoids, upper trapezius and internal rotators (i.e., pectorals and latissimuss dorsi) are often targeted among weight-training participants. In regards to external rotator and lower trapezius strength we were uncertain as to the direction of our hypothesis given previous research among male RWT participants that reported no significant difference (33). One explanation for the difference in our results was that of participant gender because all of our participants were women compared to men in the aforementioned study.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…This result was anticipated to occur from a training effect as the deltoids, upper trapezius and internal rotators (i.e., pectorals and latissimuss dorsi) are often targeted among weight-training participants. In regards to external rotator and lower trapezius strength we were uncertain as to the direction of our hypothesis given previous research among male RWT participants that reported no significant difference (33). One explanation for the difference in our results was that of participant gender because all of our participants were women compared to men in the aforementioned study.…”
Section: Discussioncontrasting
confidence: 55%
“…In an exploratory investigation among men who participated in weight training, 60% of the subjects reported having shoulder pain in the past year with 28% reporting pain within the past 3 days during weight training (31). Although shoulder injuries attributed to weight training have been reported in the literature (22,23,25,33,38,44,54), the specific adaptations and stresses imposed on the shoulder complex as a result of training practices have not been sufficiently investigated.…”
Section: Introductionmentioning
confidence: 99%
“…strict press, push press or jerk) by these athletes. Kobler and colleagues [39] suggested that the susceptibility of the shoulder complex to weight training injury is in part due to the high compressive loads these exercises apply to a traditionally non-weight bearing joint. Furthermore, the bench and overhead presses may place the shoulder in somewhat unfavorable positions, such as end-range external rotation while under heavy loads, predisposing the shoulder to both acute and chronic injuries [39,40].…”
Section: Anatomical Locationmentioning
confidence: 99%
“…That produces obvious gains in strength and hypertrophy, subsequently neglecting the smaller muscles responsible for stabilization. This biased exercise selection creates joint and muscle imbalances, thus may place participants at-risk for (Kolber, Beekhuizen, Cheng, & Hellman, 2010;Kim, Kwon, Kim, Park, Choung, & Weon, 2014). Traditional and unstable push-ups have been used for years to improve muscle performance/rehabilitation of the of the shoulder musculature (Youdas, Budach, Ellerbusch, Stucky, Wait, & Hollman, 2010).…”
Section: Introductionmentioning
confidence: 99%